Primary Aldosteronism and Metabolic Syndrome - Fallo, F.; Pilon, C.; Urbanet, R. (Hormone and Metabolic Research, 2012)
Hypertension is frequently associated with interrelated risk factors of metabolic origin, including abdominal obesity, dyslipidemia, and alterations in glucose homeostasis, all promoting the pathogenesis of arteriosclerosis. Clustering of these risk factors, defined as metabolic syndrome, is associated with an overall high cardiovascular risk profile. This article reviews current knowledge regarding the prevalence and characteristics of the metabolic syndrome in primary aldosteronism, and discusses a possible pathophysiological link between aldosterone and its individual components other than hypertension. An abnormal glucose metabolism due to insulin resistance appears to be linked to aldosterone overproduction, and seems the major contributor to metabolic dysfunction in primary aldosteronism. Impairment of insulin action may be also due to concurrent environmental factors (hypokalemia?), and/or it might occur in compartments other than fat tissue (liver? skeletal muscle?). Higher rates of cardiovascular events reported in primary aldosteronism could be due in part to the increased prevalence of the metabolic syndrome in this disorder. Regression of glucometabolic complications after the cure of aldosterone excess should be confirmed by larger studies, and the influence on the natural history of primary aldosteronism by using agents potentially able to correct metabolic abnormalities should be further explored.
Keywords: aldosterone; hypertension; obesity; lipids; diabetes